PEMBATALAN SERTIPIKAT AKIBAT TUMPANG TINDIH PEMILIKAN TANAH (STUDI DI WILAYAH KELURAHAN SIMPANG TIGA KECAMATAN BUKIT RAYA RIAU): Cancellation of Certificates Due to Overlapping Land Ownership (Study in Simpang Tiga Village, Bukit Raya District, Riau) - Shakila Arivia Azhari; Novina Sri Indiraharti (Faculty of Law, Universitas Trisakti, 2025)
This study aims to analyze the cancellation of land certificates due to overlapping ownership in Simpang Tiga Subdistrict, Bukit Raya District, Riau, based on the applicable laws and regulations in Indonesia. The research problem focuses on whether the issuance of Right of Use Certificates No. 619 and 52, as well as Ownership Certificate No. 13725, was in accordance with Indonesian legal provisions. Using a normative qualitative approach, this research examines the prevailing regulations, the procedures for certificate cancellation, and the social impacts arising from the land dispute. Through a case study and in-depth interviews with relevant parties, the study identifies the factors that led to the overlapping ownership, the obstacles encountered in the certificate cancellation process, and the efforts made to resolve the issue. The findings indicate that the issuance of Right of Use Certificates No. 619 and 52 and Ownership Certificate No. 13725 was legally flawed, as it was carried out without revoking the previous rights and without proper public notification, thereby constituting administrative defects.